Mesenchymal Stem Cell-Derived Extracellular Vesicles: A Novel Cell-Free Therapy for Sepsis - Cheng, Yanwei; Cao, Xue; Qin, Lijie (Frontiers in Immunology, 2020)
Sepsis remains a serious and life-threatening disease with high morbidity and mortality. Due to the unique immunomodulatory, anti-inflammatory, anti-apoptotic, anti-microbial, anti-oxidative, and reparative properties, mesenchymal stem cells (MSCs) have been extensively used in preclinical and clinical trials for diverse diseases and have shown great therapeutic potential in sepsis. However, concerns remain regarding whether MSCs can become tumorigenic or have other side effects. Extracellular vesicles (EVs) are a heterogeneous group of membrane-enclosed particles released from almost any cell and perform an important role in intercellular communication. Recently, it has emerged that EVs derived from MSCs (MSC-EVs) appear to exert a therapeutic benefit similar to MSCs in protecting against sepsis-induced organ dysfunction by delivering a cargo that includes RNAs and proteins to target cells. More importantly, compared to their parent cells, MSC-EVs have a superior safety profile, can be safely stored without losing function, and possess other advantages. Hence, MSC-EVs may be used as a novel alternative to MSC-based therapy in sepsis. Here, we summarize the properties and applications of MSC-EVs in sepsis.